Prevalenca in klinične značilnosti sindroma ohlapne šarenice, povezan z jemanjem tamsulozina - Blažič-Maležič, Mateja (Zdravniški vestnik, 2010)
Background: To determine the prevalence of patients taking tamsulosin (for treatment of benign prostatic hypertrophy) and the appearance of intraoperative floppy-iris syndrom (IFIS). Methods: This study identified patients after cataract surgery performed between November 2006-November 2008.Results: Of the 865 catarac procedures performed, 35(4 %) patients were taking tamsulosin. All the patients were men and the mean age was 71 years. A small pupil was demonstrated intraoperatively in 24 (68 %)patients, floppy-iris in 27(77 %) and iris prolapse during surgery was noted in 15 (43 %) patients. Conclusion: Patients using tamsulosin for treatment of benign prostatic hipertrophy appear to be at high risk of IFIS during cataract surgery, which may be associated with increased complications in cataract surgery.
Keywords: Cataract Extraction; Chemically Induced; Drug Therapy; Intraoperative Complications; Intraoperative komplikacije; Iris Diseases; katarakta; Katarakta, ekstrakcija; oftalmologija; Prostata, hiperplazija; Prostatic Hyperplasia; šarenica; Šarenica, bolezni; tamsulozin; therapy; zapleti; zdravljenje